PERAN DHARMADUTA DAN METODE PEMBABARAN DHARMA - Saputro Edi Hartono (Akademika: Jurnal Keagamaan dan Pendidikan, 2023)
Every religion needs students who are loyal, caring, and have a soul to spread the teachings of their religion, and have good competence to carry out their duties. Efforts to spread religion are known as da'wah. Each religion has its own understanding of dharmaduta. In Buddhism, the propagator of the religion is called Dharmaduta. Compared to other followers of religion, Buddhists are known to be less aggressive in spreading their religious teachings. The method used by the authors in this research is the literature review research method, which means the researcher examines from various books as a research source. The method used is the interpretation of texts in the Tripitaka holy book and various studies. To carry out the duties of Dharmaduta, appropriate competencies are needed so that the teachings can be conveyed properly and can be well understood by the recipients of the teachings. The efforts of the Buddhist dharmaduta will benefit both the teacher and the recipient of the teachings. Dharmaduta is obliged to change the new paradigm in the spread of Buddhism, which was originally oriented towards suffering to become an approach to happiness. This conclusion is in line with the nature of Buddha's existence in this universe which teaches all human beings how to eliminate suffering to achieve happiness.